Hungarian Monitoring, 3 November 1990 . [Magyar rádiófigyelő], 1990. november 3 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Crisis in Moldavia - Gorbachev on the dissolution of the Warsaw Pact headquarters Domestic Affairs: - Warsaw Pact agreement in Hungary - Hostile intelligence agents in Hungary - Reburial of Anna Kéthly - IMF on the taxi drivers' blockade - Dangers of Serbian nationalism for the Hungarian minority - Croats of Hungary hold congress in Szombathely Economy: - State budget deficit could end up out of control - Stalls in Soviet mineral oil transports Külpolitika: - Válság Moldáviában - Gorbacsov a VSZ főparancsnokságának feloszlatásáról Belpolitika: - VSZ megállapodás Budapesten - Ellenérdekű hírszerzők Magyarországon - Kéthly Anna újratemetése - Az IMF a taxis blokádról - A szerb nacionalizmus veszélyei a magyar kisebbségre - Magyarországi horvátok kongresszusa Szombathelyen Gazdaság: - Elszabadulhat az államháztartási hiány - Szovjet kőolajszállítások akadozása